Subject of the contract for travel services - Чуднов, Василь Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article deals wit the subject of the contract for travel services from positions of adaptation national legislation and the needs of its universalization and harmonization. At comparison of concepts «tourism product» and «travel services» priority is given to the latter. At the same time the author indicates on complexity and promiscuity of the subject of this contract and its variants.